2016
DOI: 10.1002/jmri.25158
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐Weighted imaging and diffusion tensor imaging detect delayed graft function and correlate with allograft fibrosis in patients early after kidney transplantation

Abstract: Combined DTI and DWI detected allograft dysfunction early after kidney transplantation and correlated with allograft fibrosis. J. Magn. Reson. Imaging 2016;44:112-121.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 37 publications
10
84
0
Order By: Relevance
“…The tractography‐based parameters of all models are most similar to those of the medulla, which is in agreement with the widely accepted belief that diffusion anisotropy originates in the radially oriented structures in the medulla 4, 5, 6, 7, 8, 9, 10, 12, 13, 14, 27. However, tract‐based FA is significantly higher than ROI‐based FA in the medulla.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The tractography‐based parameters of all models are most similar to those of the medulla, which is in agreement with the widely accepted belief that diffusion anisotropy originates in the radially oriented structures in the medulla 4, 5, 6, 7, 8, 9, 10, 12, 13, 14, 27. However, tract‐based FA is significantly higher than ROI‐based FA in the medulla.…”
Section: Discussionsupporting
confidence: 85%
“…The higher diffusion anisotropy is usually attributed to the radial organization of tubules and vasculature in the renal pyramids 1, 4, 5, 6, 7, 8, 9, 11. In addition, it has been shown that it is possible to differentiate between healthy and diseased tissue using diffusion tensor MRI parameters MD and FA, for example, in follow‐up of kidney transplants12, 13 and in the early detection of diabetic nephropathy 14…”
mentioning
confidence: 99%
“…Several studies from the research group of Hueper et al, using a kidney transplantation animal model, have shown promising results for the use of MR after transplantation [16][17][18][19]. This same research group and several others have initiated studies to translate these outcomes to the clinical setting, showing significant associations between renal allograft function and several MRI sequences in small and heterogeneous cohorts [20][21][22][23][24]. These outcomes have not yet been validated in a larger and more homogenous population of renal transplant recipients and have therefore not yet been introduced to clinical protocols for post-transplant follow-up.…”
Section: Lessons Learntmentioning
confidence: 99%
“…Applying a diffusion weighting (indicated by the b-value) causes loss of signal which is proportional to the ADC and can be modeled using a mono-exponential function. Seven studies investigated mono-exponential DWI in kidney transplantation patients (Table 4) (Thoeny et al, 2006; Blondin et al, 2011; Hueper et al, 2011, 2016; Lanzman et al, 2013; Park et al, 2014; Fan et al, 2016) Next to the microscopic diffusion of water the signal measured in DWI is also sensitive to the microcirculation. As such, the measured ADC using low b-values reflects both diffusion and perfusion and the signal can be better described using a bi-exponential model that accounts for contribution of both compartments, which is also known as Intravoxel incoherent motion (IVIM) imaging.…”
Section: Clinical Experience With Functional Mri In Kidney Allograftsmentioning
confidence: 99%